TRANSFORMASI KONSEP MUSYTARAKAH PADA ADAT WARIS ISLAM BANJAR - Jaidi, Muhammad (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
This research focuses on the transformation of the musytarakah concept within the inheritance customs of Banjar Islam. The selection of this topic is based on the importance of understanding how the principles of justice in inheritance distribution can be applied in the local context of the Banjar community. The hypothesis of this study is that the musytarakah concept introduced by Umar bin Khattab can be adapted and applied in the Banjar's badamai customs to resolve inheritance disputes fairly. The research method used is a descriptive qualitative analysis with a case study approach in the Banjar community. The results of the study show that the musytarakah principle, which emphasizes justice and dispute resolution, can be applied in badamai customs, although there are some differences in the implementation mechanisms. This transformation demonstrates that the musytarakah concept can be adjusted to local social and cultural norms, providing an effective solution to inheritance distribution issues.